2001
DOI: 10.1002/ccd.1146
|View full text |Cite
|
Sign up to set email alerts
|

Minor myocardial injury after elective uncomplicated successful PTCA with or without stenting: Detection by cardiac troponins

Abstract: Cardiac troponins are sensitive and specific markers for the detection of minor myocardial injury. However, they have been rarely used to monitor myocardial injury after coronary stenting. The purpose of the study was to measure cardiac troponin I (cTnI) and cardiac troponin T (cTnT) levels after elective uncomplicated successful percutaneous transluminal coronary angioplasty (PTCA) with or without coronary stenting and to compare their results with serum creatinine kinase MB isoenzyme (CKMB). CTnI and cTnT le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 29 publications
0
23
0
3
Order By: Relevance
“…Troponin T (TnT) and troponin I (TnI) are regarded as the featured indicators in slight cardiac injuries. [3,4] Changes in levels of tumor necrosis factor (TNF)-alpha might be determined due to myocyte damage secondary to cardiac spasm-traumatic cardiac injuries. [5] Ideal trauma grading systems should target the correct definition of all damage and the severity of each type of damage.…”
Section: Resultsmentioning
confidence: 99%
“…Troponin T (TnT) and troponin I (TnI) are regarded as the featured indicators in slight cardiac injuries. [3,4] Changes in levels of tumor necrosis factor (TNF)-alpha might be determined due to myocyte damage secondary to cardiac spasm-traumatic cardiac injuries. [5] Ideal trauma grading systems should target the correct definition of all damage and the severity of each type of damage.…”
Section: Resultsmentioning
confidence: 99%
“…Such events induce extensive inflammation of non-infarcted myocardium surrounding small islets of myocardium necrosis. [63][64][65][66][67] New areas of myocardial necrosis have been demonstrated by MRI following PCI. 68 A separate subcategory of myocardial infarction is related to stent thrombosis as documented by angiography and/or autopsy.…”
Section: Myocardial Infarction Associated With Revascularization Procmentioning
confidence: 99%
“…They concluded that minor myocardial injury is not uncommon after PTCA with or without stenting and cTn-I is more sensitive marker for the detection of this minor myocardial injury. 10 Moreno et al 17 demonstrated that at least one adverse event occurred during the stent implantation procedure in 34% of the cases; of which 38% had subsequent elevated TnI levels. They carried out the study by collecting data from 147 consecutive patients who had undergone percutaneous coronary revascularization by means of stent implantation and had clinically and angiographically satisfactory results.…”
Section: Diagnostic Use Of Troponinmentioning
confidence: 99%
“…The purpose of the study was to measure cardiac troponin-I (cTnI) level after elective uncomplicated successful percutaneous transluminal coronary angioplasty (PTCA) with or without stenting. 10 …”
Section: Diagnosis Of Minor Myocardial Injurymentioning
confidence: 99%